MicroRNA a epigenetika nádorů: makrorevoluce - Davalos, Veronica; Esteller, Manel (Current Opinion in Oncology (České vyd.), 2010)
Since the first demonstration of microRNA (miRNA) roles in tumorigenesis, a multitude of studies have established a solid scaffold that supports the increased and accelerated progression in this field. The aim of this article is to comment on the most recent findings of miRNAs in cancer, particularly focusing on epigenetics and the potential clinical applications derived from comprehensive and exhaustive research carried out during the last years. RECENT FINDINGS: A global reduction of miRNA levels is emerging as a common hallmark of cancer. Several strands of evidence have shown that one of the mechanisms responsible for this deregulation is the epigenetic silencing of miRNA genes. In turn, recent studies have revealed that some miRNAs directly repress enzymes of the epigenetic machinery, including DNA methyltransferases, histone deacetylases and histone methyltransferases. These facts broaden the promising biomedical uses of miRNAs. Apart from epigenetic mechanisms, other causes of miRNA deregulation in cancer are also discussed in this review, as well as novel clinical applications of miRNAs in cancer treatment. SUMMARY: The ability of individual miRNAs to regulate multiple target genes, implicated in turn in several pathways, confers them an extraordinary capacity as multifunctional tools for cancer therapy. Thus, restoration of the level of a single or few pleiotropic miRNAs could eventually re-establish molecular pathways altered in cancer, providing a more effective therapeutic strategy. However, further studies will be needed to validate the preliminary successful results of miRNA-based therapy obtained in cellular and animal models. Also, it is crucial to expand our knowledge about the molecular regulation of the miRNome (global miRNA expression levels) in physiological and pathological settings.
Keywords: terapie zhoubných nádorů; MicroRNAs; Animals; lidé; klinické použití; epigeneze genetická; Financing, Organized; financování organizované; nádory; Humans; zvířata; Neoplasms; mikro RNA; Epigenesis, Genetic; miRNom